ROLE OF EMOTIONAL INTELLIGENCE IN STIMULATING KNOWLEDGE SHARING BEHAVIOUR IN THE ORGANIZATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The purpose of this paper is to probe into the role of Emotional Intelligence in knowledge sharing behaviour. Seeking to support a leader’s cognitive, emotional and physical resources, the use of Emotional Intelligence is a modern tool of effective management, enabling the individual to manage a wide range of employees that are often performing in a unique set of roles. In addition, emotional and personal competencies are two primary factors that are shown to be directly linked to performance within a work environment, making the Emotional Intelligence identification and analysis essential for effective knowledge sharing as well as the increased development of the organization’s human capital. With tighter budgets, escalating costs and the continuous demand to produce more for less, there is a need to develop a higher standard for knowledge sharing behaviour, ones that will effectively address the challenges of high employee turnover, a rapidly changing business environment and the ever increasing demand for improved products and services. The study is based on examining the most generally applied definitions and other aspects of Emotional Intelligence, as well as its associated managerial leadership competencies in knowledge sharing. The paper adopted an empirical methodology in describing Emotional Intelligence leadership for effective knowledge sharing in the organization. The Emotional Intelligence leadership discussed in this paper requires that for effective knowledge sharing, organizations have to grow emotional capital to handle issues of low morale, organizational stress, high staff turnover and lack of work/ life balance. The aim of the present paper is to explore the relationship between Emotional Intelligence and knowledge sharing to measure the tendency of emotional control of the working class both male and female at a managerial level in a private and public sector of petrochemicals in India. The main task of this study is to find out the impact of different factors of emotional intelligence on knowledge Sharing. Sample statistical members of this research were 210 people. Convenience sampling technique is used to answer the instrument of the study. SPSS software was used to analyse the data collected based on descriptive statistics viz., mean, standard deviation, and percentage. The reliability and validity of the questionnaire is tested using cronbach alpha test with the derived value 0.814. Research hypothesis was reviewed using a structural equation model. The respective results have revealed that Emotional Intelligence has a positive and significant effect on the knowledge sharing behavior in the organization.